Applying Unoccupied Aircraft Systems to Study Human Behavior in Marine Science and Conservation Programs - Nowlin, Michelle B.; Roady, Stephen E.; Newton, Everette; Johnston, David W. (Frontiers in Marine Science, 2019)
The declining costs of Unoccupied Aircraft Systems (UAS, aka drones), their ease of use, and their ability to collect high resolution data from a variety of sensors has resulted in an explosion of applications across the globe. Scientists working in the marine environment are increasingly using UAS to study a variety of topics, from counting wildlife populations in remote locations to estimating the effects of storms and sea level rise on shorelines. UAS also provide transformative potential to study the ways in which humans interact with and affect marine and coastal ecosystems, but doing so presents unique ethical and legal challenges. Human subjects have property rights that must be respected, and they have rights to privacy, as well as expectations of privacy and security that may extend beyond actual legal rights. Using two case studies to illustrate these challenges, we outline the legal and regulatory landscapes that scientists confront when people are their primary study subjects, and conclude with an initial set of legal best practices to guide researchers in their efforts to study human interactions with natural resources in the marine environment.